A case study on dol net fishing operation and its economic analysis off Gujarat, north-west coast of India - Sikotariya, K. M.; Temkar, G. S.; Abdul Azeez, P.; Mathew, K. L. (Indian Journal of Fisheries, 2018)
Dol net is traditionally used for fishing along the north-west coast of India. In this study, the operational as well as economic aspects of dol net operation off Navabandar, Gujarat was studied. Dol nets operations from mechanised boats locally called as Van along Navabandar coast were considered for the present study. The overall length (OAL) of the mechanised vessels were in the range, 10-12.8 m with 2.4-3.6 m breadth and 1-1.8 m height. The total capacity of vessels was in the range 15-20 t and average fish holding capacity was 2.5 t. The fishing vessels had six cylinder engines of 87 to 105 hp. Fishermen themselves fabricated the nets for the dol net, which had seven different parts with various lengths. Kaba-sus system using steel pipes was the method of dol net fishing off Navabandar. They were locally known as Bochi, Patiya, Aor, Trijo, Bangu, Chothi and Jalo. The study indicated that the profit of a dolnetter at Navabandar in a year was `2,88,122.